Computer simulation of fuel consumption in driving cycles - Bautista, Gino T.
A computer model for simulating fuel consumption of a road vehicle was developed using steady-state performance data from chassis dynamometer tests. This original method is simple and does not require sophisticated chassis dynamometer test facilities used in more advanced countries. The method also eliminates variances due to driving style. It was determined that the predictions of the computer model agree closely with fuel consumption figures from actual road tests. The use of steady-state performance data from chassis dynamometer tests was found to be suitable in predicting fuel consumption of driving cycles. This study and its conclusions are limited to diesel engine driven road vehicles.